2019
DOI: 10.3201/eid2509.181884
|View full text |Cite
|
Sign up to set email alerts
|

Climate Classification System–Based Determination of Temperate Climate Detection ofCryptococcus gattiisensu lato

Abstract: We compared 2 climate classification systems describing georeferenced environmental Cryptococcus gattii sensu lato isolations occurring during 1989–2016. Each system suggests the fungus was isolated in temperate climates before the 1999 outbreak on Vancouver Island, British Columbia, Canada. However, the Köppen-Geiger system is more precise and should be used to define climates where pathogens are detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Until recently the geographic distribution of C. gattii was thought to be limited to tropical and subtropical areas in South America, Africa, Asia, and Australia. However, it has recently been identified in Mediterranean regions of Europe and an outbreak of cryptococcosis in the Pacific Northwest revealed that C. gattii was endemic in areas of the USA [ 42 , 43 , 44 , 45 ]. How it arrived in these geographies is unclear, but anthropomorphic factors such as trade in agricultural products (including trees and livestock), human transmission and natural transmission of spores on air currents by migratory birds and even distribution via tsunamis have been suggested [ 46 ].…”
Section: How Climate Change Could Affect Species Commonly Associated With Infections Of Humansmentioning
confidence: 99%
“…Until recently the geographic distribution of C. gattii was thought to be limited to tropical and subtropical areas in South America, Africa, Asia, and Australia. However, it has recently been identified in Mediterranean regions of Europe and an outbreak of cryptococcosis in the Pacific Northwest revealed that C. gattii was endemic in areas of the USA [ 42 , 43 , 44 , 45 ]. How it arrived in these geographies is unclear, but anthropomorphic factors such as trade in agricultural products (including trees and livestock), human transmission and natural transmission of spores on air currents by migratory birds and even distribution via tsunamis have been suggested [ 46 ].…”
Section: How Climate Change Could Affect Species Commonly Associated With Infections Of Humansmentioning
confidence: 99%
“…The spatial methodological framework presented here was successfully used in a recent study to determine the risk zones in Europe to different cryptococcal pathogens ( Alaniz et al, 2020 ). The suitable geographic areas for C. bacillisporus survival are characterized by scarce or null rainfall during the dry season and moderate rainfall during the cold season, high SR and scarce vegetation corresponding to the warm summer Mediterranean climate present in California and northwestern Mexico ( Acheson et al, 2019 ). The same climatic conditions are present in Central Chile, where the C. bacillisporus isolate was recovered, suggesting that VGIII is spreading outside the endemic areas and is potentially able to colonize a wide area in Chile covering about 150,000 km 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike cryptococcosis caused by the yeasts belonging to the C. neoformans species complex, which affects mostly immunocompromised hosts, C. gattii species complex strains also have the capacity to affect immunocompetent hosts as reported by recent studies ( Mcmullan et al, 2013 ; Chen et al, 2014 ; Li et al, 2020 ). The C. gattii species complex has largely been historically restricted to tropical and subtropical regions, however records from 1990 in San Francisco California (United States), suggest their expansion into temperate zones in America ( Pfeiffer and Ellis, 1991 ; Acheson et al, 2019 ). Since then, the most important outbreaks in the temperate zone were British Columbia Canada and the Northwest Pacific coast of the United States both in 1999, affecting immunocompromised and immunocompetent hosts and generating a public health alarm ( Espinel-ingroff and Kidd, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The members of the C. gattii species complex are emerging pathogens and were initially considered as ‘tropical and subtropical pathogens’ [ 5 ]. However, studies from the past two decades showed that infections and environmental occurrence has expanded to temperate regions, including North America and the north-western part of Europe [ 6 , 7 ]. In addition, many ecological niches have been investigated worldwide in an attempt to elucidate the environmental reservoirs [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%